2023
DOI: 10.3390/jcm12072580
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic Imbalances in Seizures and Epilepsy of Paediatric Age: A Literature Review

Abstract: Cerebral excitability and systemic metabolic balance are closely interconnected. Energy supply to neurons depends critically on glucose, whose fluctuations can promote immediate hyperexcitability resulting in acute symptomatic seizures. On the other hand, chronic disorders of sugar metabolism (e.g., diabetes mellitus) are often associated with long-term epilepsy. In this paper, we aim to review the existing knowledge on the association between acute and chronic glycaemic imbalances (hyper- and hypoglycaemia) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…It is also important to consider the impact that all these metabolic disturbances might have on the behavioural phenotypes and the occurrence of seizures found in Fus Δ14/Δ14 mice (both sexes). Seizures are observed in over 200 different metabolic diseases ( Rahman et al, 2013 ; Almannai et al, 2021 ), by multiple mechanisms, including neurotransmission alterations and energy deficiency and hypoglycaemia ( Bartolini et al, 2023 ). Cognition and behavioural alterations are also known to be greatly influenced by metabolic alterations ( Tanaka et al, 2020 ; Morys et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider the impact that all these metabolic disturbances might have on the behavioural phenotypes and the occurrence of seizures found in Fus Δ14/Δ14 mice (both sexes). Seizures are observed in over 200 different metabolic diseases ( Rahman et al, 2013 ; Almannai et al, 2021 ), by multiple mechanisms, including neurotransmission alterations and energy deficiency and hypoglycaemia ( Bartolini et al, 2023 ). Cognition and behavioural alterations are also known to be greatly influenced by metabolic alterations ( Tanaka et al, 2020 ; Morys et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since recent studies have shown significant differences in the abundance of amino acids in different anatomical regions of the brain [36], we anticipate that transient fluctuations in specific amino acids may sensitize people with GATOR1 mutations to seizures at the variable foci associated with GATOR1-dependent familial focal epilepsies (FFEVFs) [1,34]. Neurologically, these deficiencies may occur at discrete times when nutrients are limited, which may provide a rationale for the association of GATOR1 with nocturnal seizures [34,37,38], similar to seizures caused by poor glycemic control in diabetes [39]. Other processes downstream of mTORC1 signaling could further exacerbate cellular defects, at least in part due to a deficiency in TFEB-dependent gene expression and lysosomal function [25,40].…”
Section: Discussionmentioning
confidence: 99%
“… 15 One of the hypotheses in humans is that acute hypoglycemia affects high metabolic‐demand brain sites, such as the mesial temporal lobe and the peri‐rolandic cortex, and it triggers motor presentations of seizures. 16 Although the appearance of hypoglycemic symptoms also depends on the glucose concentration, the threshold for glucose levels associated with seizures is unclear. 15 Our current study showed no difference in the initial glucose levels between patients with and without seizures.…”
Section: Discussionmentioning
confidence: 99%